NUMERICAL THERMAL FIELD ANALYSIS IN REDUNDANT ELECTRIC MOTORS (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2024)
In this paper, we propose to analyze the heat transfer of a torque motor with a limited angle under special space conditions. Three-dimensional models will be used, and two current values will be considered in numerical analysis. Variants in which the boundary conditions will consider different values of the emissivity of engine surfaces will also be considered. Inside the stator and rotor subassemblies of the motor, heat transfer will be carried out by conduction and radiation between the motor and the ambient environment. Using numerical analysis, it will be possible to determine the time during which the temperature in the winding reaches the maximum allowable value for the limited angle torque motor under the mentioned conditions.
Keywords: Limited angle torque motor; Numerical analysis; Finite element (FEM)